Need help asap!

p and q are the solutions to the quadratic equation x^2 + 4x + 6 = 0.


p^2 and q^2 are the solutions to the quadratic equation x^2 + bx + c = 0.


Find b + c.

Respuesta :

Answer:

p+q= -4

Step-by-step explanation:

If 'p' and 'q' are solutions to x^2 + 4x +6=0 then that same eq. can be written as (x-p)*(x-q).

Hence we have the following relationship

(x-p)*(x-q)=x^2 + 4x +6

Distributing terms x^2 -xq-xp+pq=x^2 + 4x +6

We have obtained 2 equations if we look at the coefficients of the quadratic equation:

From x coefficients we have the equation: -p-q=4

and from independent terms we have: p*q= 6

From the first eq. we have -(p+q)=4, so p+q= -4